Change of the components of nonspecific protection of respiratory system in diabetes mellitus - Pivovarova, O. A. (Zaporozhye Medical Journal, 2014)
Aim. System of nonspecific respiratory protection factors in diabetes is currently insufficiently studied. Methods and results. 63 diabetic patients and 46 healthy individuals passed diagnostic bronchoscopy. Histological examination of the respiratory system in experimental diabetes mellitus have been done in 47 rats and 43 intact animals (male) line Wistar. Conclusion. Mechanisms of nonspecific protection of the respiratory system in insulin deficiency, neutrophil activity and inhibition of the functional activity of epithelial cells and alveolar macrophages were established.